PENGARUH STRATEGI CUSTOMIZATION TERHADAP KINERJA PERUSAHAAN MELALUI PENGGUNAAN KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN (Studi Empiris pada Perusahaan Manufaktur di Provinsi Riau) - Edwin Setiawan; Desmiyawati Desmiyawati; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of Customization Strategy to Firm Performance Characteristics of through the use of Information Systems Management Accounting in a manufacturing company in Riau Province. The population used in this study is a manufacturing company that originates in theCentral Bureau of Statistics of the Republic of Indonesia Representative Riau Province (BPS Indonesia Riau Province) as many as 32 companies. Sampling was done by using purposive sampling method, ie a total of 32 manufacturing companies that have registered. Data analysis was performed using a hypothesis test with the help of Partial Least Square (PLS) version 2.0 m3 with a value of tstatistics generated from PLS output compared with the value of the t-table, an estimate of output PLS latent variables that are linear aggregates of indicators with a significance level of 0.05 or 5%. The result shows (1) customization strategy does not affect company performance, (2) customization strategy has positif (+) influence on usefulness of broad scope management accounting systeminformation characteristic, (3) the usefulness of broad scope management accounting system information characteristic has positif (+) impact to company performance, (4) customization strategy has positif (+) affects company performance through the usefulness of broad scope management accountingsystem information characteristic.Keywords : Customization Strategy, Firm Performance, and Broadscope.